MOLECULAR DOCKING OF CYMBOPOGON CITRATUS EXTRACTS AS POTENCY FOR DRUG FORMULATION TARGETING FUNGAL SPECIES CAUSING ONYCHOMYCOSIS IN BENUE STATE, NIGERIA - Magdalene, Tyona Ngodoo (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Onychomycosis is a fungal infection of the nails, characterized by thickening, discoloration, and brittleness. It is caused by dermatophytes, non-dermatophyte molds, and yeasts and poses a significant public health challenge, particularly in tropical regions like Nigeria. Current antifungal treatments often show inconsistent efficacy, prompting the search for alternative therapies. This study explores the potential of Cymbopogon citratus (lemongrass) extracts as antifungal agents targeting key enzymes involved in fungal pathogenesis in onychomycosis in Benue State, Nigeria. Using ethical approval and rigorous laboratory protocols, fungal samples were cultured, and the Squalene Epoxidase (SQLE) gene was identified. Phytoconstituents in C. citratus extracts were analyzed via Gas Chromatography-Mass Spectrometry. Molecular docking using the Schrodinger Glide protocol predicted interactions with SQLE, a critical enzyme for fungal ergosterol biosynthesis. Dodecanoic acid-1,2,3-propane showed the highest docking score (-65.13 kcal/mol) and a molecular weight of 638 g/mol, outperforming terbinafine (-64.39 kcal/mol, 327.9 g/mol). The compounds exhibited strong binding to SQLE, suggesting a mechanism for disrupting fungal membrane synthesis. These findings emphasize the integration of computational predictions with in vitro studies in developing effective treatments for onychomycosis, addressing a significant medical need locally and globally.